IMPACTS OF LEARNING INTEREST AND PARENTAL SUPPORT ON ACADEMIC PERFORMANCE OF SECONDARY SCHOOL STUDENTS OF ISLAMIC STUDIES IN LAGOS - Isiaq Oluwatosin Yahya; Shogbesan Yusuf Olayinka; Zakariyah Mikail Poopo (JURNAL EDUSCIENCE, 2024)
This study investigates the impacts of learning Interest and parental support on academic performance of secondary school students in Islamic Religious Studies in Lagos State. The study descriptive survey with the population consisting of all 68 public senior secondary schools in Lagos state Education District V and 31,703 Islamic Religious Studies Students. A Sample of 400 SS II Islamic religious studies students were selected using Krejcie and Morgan Sampling Template in 10 randomly selected schools for this study. Descriptive analysis was used to answer the research questions and lineal Regression was used to test hypotheses. The study found that the level of learning interest, parental support and academic performance were all high among senior secondary schools Islamic Studies Students in Lagos State. Also, the learning interest and parental support does not have significant influence on the Academic Performance of senior secondary schools Islamic Studies Students in Lagos State. Based on these findings, it was recommended among others that students should show high level of learning interest and commitment in the study of Islamic studies; Parents and guardians should show high level of parental support to their children, in order to reinforce learning and enhance their academic performance.